Co-existence of OXA-48 and NDM-1 in colistin resistant Pseudomonas aeruginosa ST235. Issue 1 (1st January 2020) - Vatansever, Cansel; Menekse, Sirin; Dogan, Ozlem; Gucer, Lal Sude; Ozer, Berna; Ergonul, Onder; Can, Fusun
ABSTRACT: Here, we presented 11 cases with colistin-resistant Pseudomonas aeruginosa infection and co-existence of OXA-48 and NDM-1 in the ST235 high-risk clone. The molecular analyses were performed by Sanger sequencing and RT–PCR. The eight patients (72.7%) had an invasive infection and three (27.3%) had colonization. The 30-day mortality rate was 87.5% (7/8). Three patients (37.5%, 3/8) received colistin therapy before isolation of P. aeruginosa . In the Multilocus sequence typing (MLST) analysis of 11 isolates, eight (72.7%) isolates belonged to P. aeruginosa ST235 clone. All isolates were NDM-1 positive, and nine isolates (81.8%) were found to be positive for both OXA-48 and NDM-1. Sequences of pmrAB and phoPQ revealed numerous insertions and deletions in all isolates. In 10 isolates pmrAB and phoPQ were found to be upregulated. In conclusion, the co-existence of OXA-48 and NDM-1 genes in colistin-resistant P. aeruginosa ST235 high-risk clone indicates the spread of carbapenemases in clinical isolates and highlights need of continuous surveillance for high-risk clones of P. aeruginosa .